The Effect of Obesity on Spirometry Tests among Healthy Non-smoking Adults - Saad, Ebrahim Mouaffak; Hejazie, Malek; Al-meri, Munif (Journal of medical and pharmaceutical sciences, 2022)
Background: Obesity is a major health problem in Syria. Obesity is associated with many diseases, including diabetes, hypertension, cardiovascular disorders, and cancer. Respiratory function is also affected. However, studies investigating pulmonary functions in obese people are few in number. Aim of the study: To study the effect of obesity on spirometry tests among healthy non-smoking adults. Participators and methods: A comparative cross-sectional study of 120 non-smoking adult participators (67 females and 53 males) attending outpatient clinics of Tishreen University Hospital in Lattakia between October 2020 and October 2021. Participators with chronic pulmonary diseases, cardiovascular diseases, and pregnancy were excluded. After a full medical evaluation, measurement of height and weight, and calculation of Body Mass Index BMI, participators were classified according to their BMI into five groups. Then, they underwent spirometry tests with measurement of forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), FEV1/FVC ratio, and peak expiratory flow (PEF). Results: All comparison groups were similar in age and sex. There were significant statistical decreases in FVC, FVC%, FEV1, FEV1% and PEF in overweight, and obesity groups comparing normal - weight group, but no significant statistical differences in FEV1/FVC ratio among all groups. Conclusion: Obesity negatively affects spirometric parameters among healthy adults.
Keywords: BMI; Obesity; Overweight; Smoking; Spirometry